A solid-state colorimetric fluorescence Pb2+-sensing scheme: mechanically-driven CsPbBr3 nanocrystallization in glass. Issue 16 (17th April 2020) - Zhang, Liqiang; Lin, Hang; Wang, Congyong; Liu, Wei-Ren; Li, Shuxing; Cheng, Yao; Xu, Ju; Gao, Hang; Li, Kang; Copner, Nigel; Chen, Xueyuan; Wang, Yuansheng
Abstract : Herein, it is proposed a brand-new solid-state Pb 2+ -sensing strategy based on mechanically-driven glass crystallization in a Pb 2+ -responsive borate glass system. Abstract : Highly toxic Pb 2+ poses a great threat to the health of human beings and ecosystems, urgently calling for an efficient Pb 2+ detection method. Herein, we demonstrated a brand-new solid-state fluorescence Pb 2+ -sensing scheme based on a type of Pb 2+ -responsive borate glass powder that is able to precipitate CsPbBr3 nanocrystals on the glass surface upon grinding with Pb 2+ sources, following a mechanically driven glass crystallization mechanism. Pb 2+ sensing is achieved via the Pb 2+ concentration-dependent green emission of CsPbBr3 as an indicator signal and independent red emission of Eu 3+ as a reference signal. Under UV light irradiation, the obvious emissive color variation from red to green as Pb 2+ concentration varies enables the intuitive Pb 2+ -sensing by naked eyes. With the aid of a spectrometer and smartphone, Pb 2+ concentration can be quantitatively determined with the detection limit as low as ∼70 ppm and ∼400 ppm, respectively. The semi-quantitative Pb 2+ detection is also possible by comparing the emissive color with the calibrated color card. Hopefully, the proposed solid-state fluorescence Pb 2+ -sensing strategy with high selectivity can be used for portable and quick Pb 2+ analysis in daily life.